Geochemical Characteristics and Sedimentary Environment of the Upper Permian Longtan Coal Series Shale in Western Guizhou Province, South China. (11th October 2021) - Zhao, Lingyun; Zhou, Peiming; Lou, Yi; Zhao, Youzhou; Liu, Wei; Liao, Zhiwei; Xia, Peng
Abstract : China's marine-continental transitional facies shale gas resources are abundant with shale gas resources of about 19.8 trillion cubic meters, while the exploration and development of these shale gas resources are still in the initial stage. The Upper Permian Longtan coal series shale is one of the most important transitional shales in the Yangtze platform, China. In this study, the comprehensive methods of mineralogy and organic geochemistry are used to discuss the characteristic of organic matter and sedimentary environment of the Longtan coal series shale in western Guizhou Province, South China. The results show that (1) the total organic carbon (TOC) content of this shale ranges in 0.6%-28.21%, mainly in 3%-12%, indicating a "good-excellent" hydrocarbon source rock, and its vitrinite reflectance (R o ) ranges from 1.48% to 2.93%, indicating a high-overmature organic matter; (2) the organic matter in this shale is multiorigin, and most of them come from the terrestrial higher plant while the rest come from the plankton; (3) type index (TI) of organic matter is from -65 to 41, indicating most of the kerogens which are II1 -III types; and (4) the sedimentary environment of this shale is dominated by suboxic-anoxic fresh water environment, which provides a favorable condition for the preservation of organic matter. In addition, the warm and humid climate during the Late Permian in the Yangtze platform promotes plant growth, and as a result, the Longtan coal series shale is rich in organic matter and has great potential of shale gas exploration and development.